Moisture-wicking medical dressing and method of making same
Patent Information
- Application Number
- CN202511052162.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-29
AI Technical Summary
[0007]本发明的目的在于提供一种吸湿排汗的医用敷料及其制备方法,以解决上述背景技术中提出的伤口感染与愈合缓慢的问题技术问题
[0033]1.本发明通过引入聚乙醇酸基非异氰酸聚氨酯共聚酯、左氧氟沙星,将左氧氟沙星均匀分散嵌入纤维网络中,实现了抗菌药物的均匀分散与可控释放,有效抑制伤口处细菌的生长和繁殖,解决了伤口感染与愈合缓慢的问题,提高了愈合速度并降低了并发症风险;
Smart Images

Figure CN120789321B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical dressing technology, specifically to a moisture-wicking medical dressing and its preparation method. Background Technology
[0002] Medical dressings are medical materials used to cover and protect wounds and promote wound healing, playing a vital role in clinical treatment. They effectively isolate wounds from the external environment, prevent bacterial infection, and provide a suitable healing environment.
[0003] Traditional medical dressings, such as gauze and bandages, can protect wounds to some extent, but they have drawbacks such as short antibacterial period and poor water absorption. They cannot effectively absorb wound exudate, increasing the risk of infection and causing problems such as wound infection and slow healing.
[0004] Patent CN103007339B discloses a biological powder medical dressing and its preparation method. The above patent is applicable to wounds of various shapes, is beneficial to the growth of new tissue, promotes wound healing, and reduces the difficulty of debridement and the patient's pain when changing dressings.
[0005] The above-mentioned patent uses biomaterials for formulation, which has good biocompatibility and can be degraded and absorbed by the human body. It solves the problems of complex preparation methods and unreliable safety of existing powder dressings. However, there is still room for optimization in terms of the continuous antibacterial properties of medical dressings. This application solves the problems of wound infection and slow healing.
[0006] Therefore, this application proposes a medical dressing that achieves continuous antibacterial properties and moisture-wicking, and a method for preparing the same. Summary of the Invention
[0007] The purpose of this invention is to provide a moisture-wicking medical dressing and its preparation method, so as to solve the technical problems of wound infection and slow healing mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a moisture-wicking medical dressing, comprising a polyurethane copolyester nanofiber membrane, wherein the preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0009] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0010] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0011] Preferably, the non-isocyanate polyurethane copolyester comprises the following components by weight: 80-100 parts of non-isocyanate polyurethane, 5-20 parts of polyglycolic acid diol, 1-5 parts of chain extender, and 0.5-5 parts of catalyst. The preparation method of the non-isocyanate polyurethane copolyester includes the following steps:
[0012] Non-isocyanate polyurethane and polyglycolic acid diol were poured into hexafluoroisopropanol, stirred and heated to 60°C. When no liquid dripped from the condenser outlet, chain extender and catalyst were added. Heating was stopped after 0.5 h to obtain the reactants.
[0013] The reactants were washed with deionized water and then placed in a vacuum drying oven and dried at 100°C for 24 hours to obtain a non-isocyanate polyurethane copolyester.
[0014] Preferably, the method for preparing the chitosan-gelatin-glycerol mixed solution includes the following steps:
[0015] Chitosan powder was poured into an acetic acid aqueous solution to prepare a chitosan mixed solution. Gelatin powder was poured into deionized water to prepare a gelatin solution. The chitosan mixed solution and the gelatin solution were mixed to obtain a chitosan-gelatin mixed solution.
[0016] Glycerin was added to the chitosan-gelatin mixed solution and stirred to obtain the chitosan-gelatin-glycerin mixed solution.
[0017] Preferably, the preparation method of the spermidine crosslinking agent includes the following steps:
[0018] Remove spermidine from the refrigerator and thaw it using a water bath. Pour terephthalaldehyde into anhydrous ethanol and stir to obtain a terephthalaldehyde solution.
[0019] The thawed spermidine was poured into a terephthalaldehyde solution and stirred to obtain a spermidine crosslinking agent.
[0020] Preferably, the preparation method of the non-isocyanate polyurethane includes the following steps:
[0021] Ethylene carbonate and 1,6-hexanediamine were mixed under a nitrogen atmosphere, stirred and heated to 80°C, deionized water was added, and the mixture was frozen, recrystallized and vacuum dried to obtain hexanediamine ethylene glycol diol.
[0022] Hexamethylenediamine glycol diol and polyethylene glycol were poured into a reaction vessel, stannous chloride dihydrate was added, the mixture was stirred and heated to 220°C, and vacuum pump was used for depressurization treatment to obtain non-isocyanate polyurethane.
[0023] Preferably, the mass fraction ratio of chitosan to gelatin in the chitosan-gelatin mixed solution is 1:4, and the volume fraction ratio of chitosan-gelatin mixed solution to glycerol is 7:3.
[0024] Preferably, the preparation method of the polyglycolic acid diol includes the following steps:
[0025] Glycolic acid and neopentyl glycol are mixed, zinc acetate dihydrate and toluene are added, nitrogen gas is introduced and the mixture is heated to 120°C to obtain polyglycolic acid diol.
[0026] Preferably, the chain extender is sebacate chloride and the catalyst is triethylamine.
[0027] Preferably, the preparation method includes the following steps:
[0028] S1. Polyurethane copolyester nanofiber membrane, polylactic acid microfiber material, and viscose fiber material are sequentially stacked and subjected to hot pressing to obtain medical dressing.
[0029] Preferably, the preparation method further includes the following steps:
[0030] S11. Polylactic acid chips and molten polyethylene glycol are blended together, sodium dodecyl sulfate chips are added, and the mixture is stirred using a high-speed mixer to obtain a blended raw material.
[0031] S12. The blended raw materials are melted into polymer melt by a screw extruder, and the polymer melt is transported to the spinneret hole of the die head by a metering pump. The melt is extruded into fine streams and bonded to the receiving screen to form polylactic acid microfiber material.
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] 1. This invention introduces polyglycolic acid-based non-isocyanate polyurethane copolyester and levofloxacin, and uniformly disperses levofloxacin into the fiber network, thereby achieving uniform dispersion and controllable release of antibacterial drugs, effectively inhibiting the growth and reproduction of bacteria at the wound site, solving the problems of wound infection and slow healing, improving the healing speed and reducing the risk of complications.
[0034] 2. This invention introduces chitosan, gelatin, and glycerin. By utilizing the water-absorbing properties of glycerin and the microporous structure of the polyurethane copolyester nanofiber membrane, it achieves humidity regulation at the wound site, keeping the wound neither too wet nor too dry. This solves the problem of maintaining a balance between moisture and dryness in the wound and improves the wound healing speed.
[0035] 3. This invention forms a cross-linked network by spin-coating a chitosan-gelatin-glycerol mixture and spermidine cross-linking agent onto a polyurethane copolyester nanofiber membrane, ensuring the continuous release of the spermidine cross-linking agent, effectively reducing the local inflammatory response of the wound, and accelerating wound healing;
[0036] 4. This invention combines non-isocyanate polyurethane and polyglycolic acid diol to generate polyglycolic acid-based non-isocyanate polyurethane copolyester, which improves the tensile strength and elongation at break of the film, achieves good adhesion of medical dressings, and improves the safety and environmental friendliness of the material. Attached Figure Description
[0037] Figure 1 This is a schematic diagram of the polyurethane copolyester nanofiber membrane preparation process of the present invention;
[0038] Figure 2 This is a schematic diagram of the preparation process of the non-isocyanate polyurethane copolyester of the present invention;
[0039] Figure 3 This is a schematic diagram of the preparation process of the chitosan-gelatin-glycerol mixed solution of the present invention;
[0040] Figure 4 This is a schematic diagram of the preparation process of the spermidine crosslinking agent of the present invention;
[0041] Figure 5 This is a schematic diagram of the preparation process of the non-isocyanate polyurethane of the present invention;
[0042] Figure 6 This is a schematic diagram of the preparation process of polyglycolic acid diol according to the present invention;
[0043] Figure 7 This is a schematic diagram of the polylactic acid microfiber material preparation process of the present invention;
[0044] Figure 8 This is a schematic diagram of the medical dressing preparation process of the present invention. Detailed Implementation
[0045] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] Example 1, please refer to Figure 1A moisture-wicking medical dressing includes a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 100 parts non-isocyanate polyurethane, 20 parts polyglycolic acid diol, 5 parts chain extender, and 5 parts catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0047] Non-isocyanate polyurethane and polyglycolic acid diol were poured into hexafluoroisopropanol, stirred and heated to 60°C. When no liquid dripped from the condenser outlet, chain extender sebacate chloride and catalyst triethylamine were added. Heating was stopped after 0.5 h to obtain the reactants. The reactants were washed with deionized water and placed in a vacuum drying oven to dry at 100°C for 24 h to obtain non-isocyanate polyurethane copolyester.
[0048] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0049] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0050] Furthermore, in the preparation of polyurethane copolyester nanofiber membranes, levofloxacin was added as an antibacterial drug to the spinning solution. The spinning solution was stretched under a high-voltage electric field to form nanofibers, and levofloxacin was uniformly dispersed and embedded in the nanofibers. The polyurethane copolyester nanofibers had a diameter between 300-500 nm and a porosity >85%, providing a large drug-carrying surface area. Levofloxacin molecules were embedded in the fiber network through hydrogen bonds and van der Waals forces. In the initial burst release stage, levofloxacin was rapidly released from the fiber surface, quickly establishing an antibacterial concentration and achieving an initial high-concentration antibacterial effect. Subsequently, in the sustained release stage, the deep-layer levofloxacin drug was slowly released through fiber degradation and diffusion, forming a sustained antibacterial effect.
[0051] When a polyurethane copolyester nanofiber membrane is applied to the wound surface, levofloxacin is continuously released upon contact with the wound exudate, ensuring the drug's sustained effect in the wound area. Levofloxacin effectively inhibits bacterial proliferation and biofilm matrix synthesis by blocking the key functions of bacterial DNA double-strand breaking, cross-linking, and rejoining, thus preventing bacteria from replicating their DNA. This inhibits or directly kills the bacteria that cause infection, significantly reducing the risk of chronic wound infection and providing strong support for patient recovery. By effectively controlling wound infection, the polyurethane copolyester nanofiber membrane creates a clean and healing-promoting microenvironment for wound recovery. This environment reduces bacterial load, alleviates the inflammatory response of the wound, and avoids tissue damage caused by excessive release of inflammatory factors, achieving an indirect anti-inflammatory effect, accelerating wound healing, and reducing the risk of complications caused by infection.
[0052] By introducing polyacrylonitrile, the mechanical strength of polyurethane copolyester nanofibers is enhanced, carrier degradation is delayed, and the drug release cycle is prolonged. Hexafluoroisopropanol is used as a solvent. The fluorinated groups in hexafluoroisopropanol interact hydrophobically with the fluorinated segments of non-isocyanate polyurethane and the fluorine atoms of levofloxacin, promoting uniform drug dispersion in the spinning solution. At the same time, the fluorinated polymer reduces the surface energy of the polyurethane copolyester nanofiber membrane, reducing initial bacterial adhesion and forming a dual protection with the bactericidal effect of levofloxacin.
[0053] Example 2, please refer to Figure 1 and Figure 3 A moisture-wicking medical dressing includes a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 95 parts of non-isocyanate polyurethane, 15 parts of polyglycolic acid diol, 4 parts of chain extender, and 4 parts of catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps.
[0054] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0055] Chitosan powder was poured into an acetic acid aqueous solution to prepare a chitosan mixed solution. Gelatin powder was poured into deionized water to prepare a gelatin solution. The chitosan mixed solution and the gelatin solution were mixed to obtain a chitosan-gelatin mixed solution. Glycerin was added to the chitosan-gelatin mixed solution and stirred to obtain a chitosan-gelatin-glycerin mixed solution.
[0056] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0057] Furthermore, chitosan, as a natural polymer material, possesses excellent biocompatibility and biodegradability. Chitosan can significantly promote cell adhesion and proliferation, providing a favorable growth environment for cells. In addition, chitosan also has certain anti-inflammatory effects, effectively inhibiting the activation of inflammatory cells and the release of inflammatory factors, thereby significantly reducing the inflammatory response around the wound and promoting rapid wound healing. Meanwhile, gelatin also has good biocompatibility, promoting cell growth and tissue regeneration. During wound healing, gelatin can effectively promote the anti-inflammatory phase, accelerating wound healing. The components of chitosan and gelatin are compatible with cells... The similarity to the exomatrix provides a microenvironment similar to natural tissue for cell growth, thereby promoting the interaction between cells and the dressing. In addition, chitosan and gelatin can promote cell proliferation and differentiation by providing cells with necessary growth factors and cytokines, thus accelerating the wound healing process. Moreover, chitosan and gelatin molecules contain active functional groups such as amino and carboxyl groups, which can bind tightly to receptors on the cell surface and effectively promote cell adhesion. Glycerin has excellent water absorption properties and can effectively absorb moisture from the surrounding environment, improving the hydrophilicity and hygroscopicity of the dressing material and keeping the wound neither too wet nor too dry.
[0058] Example 3, please refer to Figure 1 and Figure 4 A moisture-wicking medical dressing includes a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 90 parts non-isocyanate polyurethane, 10 parts polyglycolic acid diol, 3 parts chain extender, and 2 parts catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0059] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0060] Remove spermidine from the refrigerator and thaw it using a water bath. Pour terephthalaldehyde into anhydrous ethanol and stir to obtain a terephthalaldehyde solution. Pour the thawed spermidine into the terephthalaldehyde solution and stir to obtain a spermidine crosslinking agent.
[0061] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0062] Furthermore, spermidine, through its unique biological activity, can effectively induce polarization transformation in macrophages. Spermine promotes the gradual transformation of M1 macrophages, which originally possess pro-inflammatory properties, into M2 macrophages with pro-repair functions, thereby reducing the expression level of pro-inflammatory cytokines at the wound site and significantly increasing the expression level of anti-inflammatory cytokines. Through a bidirectional regulatory mechanism, it effectively alleviates the inflammatory response at the wound site, creating a favorable environment for wound healing and accelerating the wound repair process. In the preparation of the medical dressing, a chitosan-gelatin-glycerol mixture is first uniformly spin-coated onto a monolayer substrate, followed by the spin-coating of spermidine onto the chitosan-gelatin-glycerol layer. The amine crosslinking agent, with its aldehyde groups, can react with the amino groups in chitosan and gelatin molecules via a Schiff base reaction, forming a stable crosslinked network structure. This crosslinked network enhances the mechanical strength and stability of the dressing and immobilizes the spermidine crosslinking agent within the dressing, ensuring its continuous and stable release during use. This sustained release of spermidine allows it to fully exert its anti-inflammatory and immunomodulatory effects, effectively inhibiting immune rejection reactions caused by the dressing itself and reducing the resulting inflammatory response. Simultaneously, spermidine can also alleviate stress-induced inflammatory responses caused by skin damage, further promoting wound healing. Through a multi-level regulatory mechanism, the anti-inflammatory effect and wound-healing potential of the medical dressing are significantly enhanced.
[0063] Example 4, please refer to Figure 1 , Figure 2 , Figure 5 and Figure 6 A moisture-wicking medical dressing includes a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 85 parts non-isocyanate polyurethane, 8 parts polyglycolic acid diol, 2 parts chain extender, and 1 part catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0064] Ethylene carbonate and 1,6-hexanediamine were mixed under a nitrogen atmosphere, stirred, and heated to 80°C. Deionized water was added, and the mixture was frozen, recrystallized, and vacuum dried to obtain hexanediamine ethylene glycol diol. Hexanediamine ethylene glycol diol and polyethylene glycol were poured into a reaction vessel, stannous chloride dihydrate was added, and the mixture was stirred and heated to 220°C. The mixture was then subjected to reduced pressure using a vacuum pump to obtain non-isocyanate polyurethane. Non-isocyanate polyurethane and polyglycolic acid diol were poured into hexafluoroisopropanol, sebacate chloride and triethylamine were added, and the mixture was washed with deionized water and dried at 100°C for 24 hours to obtain non-isocyanate polyurethane copolyester.
[0065] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0066] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0067] Furthermore, the cycloaddition reaction of ethylene carbonate with 1,6-hexanediamine produces hexanediamine glycol diol, which is then polycondensed with polyethylene glycol under stannous chloride catalysis. This avoids the use of highly toxic isocyanate monomers in traditional polyurethane synthesis, significantly improving the safety and environmental friendliness of the material. The ether bonds in the polyglycolic acid-based non-isocyanate polyurethane copolyester molecular chain form water molecule transport channels, enabling the medical dressing to quickly absorb wound exudate, achieving highly efficient moisture wicking and effectively preventing the accumulation of exudate at the wound site. The long alkyl chains introduced by sebacyl chloride construct hydrophobic microdomains, blocking the reverse permeation of liquid water, which is beneficial to wound healing.
[0068] Example 5, please refer to Figure 1 A moisture-wicking medical dressing includes a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 80 parts non-isocyanate polyurethane, 5 parts polyglycolic acid diol, 1 part chain extender, and 0.5 parts catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0069] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0070] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0071] Furthermore, the non-isocyanate polyurethane copolyester combines the flexibility of non-isocyanate polyurethane with the strength of polyglycolic acid diol. As a component, the non-isocyanate polyurethane, through the soft and hard segments in the non-isocyanate polyurethane molecular chain, endows the membrane with good toughness and strength. At the same time, the introduction of polyglycolic acid segments in the polyglycolic acid diol increases the crystallinity of the material, further improving the tensile strength and elongation at break of the membrane. This allows the polyurethane copolyester nanofiber membrane to better adhere to the wound surface, providing stable support and protection, and preventing secondary damage caused by dressing movement or detachment.
[0072] Example 6, please refer to Figure 1 , Figure 7 and Figure 8 A moisture-wicking medical dressing, comprising a polyurethane copolyester nanofiber membrane, wherein the preparation method of the medical dressing includes the following steps:
[0073] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0074] The monolayer membrane was subjected to plasma treatment, and the plasma-treated monolayer membrane was placed on a spin coater. A chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0075] Polylactic acid (PLA) chips and molten polyethylene glycol (PEG) are blended together, and sodium dodecyl sulfate (DSS) chips are added. The mixture is then stirred using a high-speed mixer to obtain a blended raw material. The blended raw material is melted into a polymer melt using a screw extruder. The polymer melt is then transported to the spinneret of the die head using a metering pump to extrude fine melt streams. These streams are then bonded onto a receiving screen to form PLA microfiber material. Polyurethane copolyester nanofiber membrane, PLA microfiber material, and viscose fiber material are then sequentially layered and subjected to hot pressing to obtain a medical dressing.
[0076] Furthermore, polylactic acid (PLA) microfiber materials prepared through meltblown molding possess excellent mechanical properties, enabling medical dressings to withstand certain external forces during use without easily breaking, thus providing stable protection for wounds. PLA microfiber materials are improved in terms of hygroscopicity and liquid management capabilities through blending with polyethylene glycol and sodium dodecyl sulfate. Simultaneously, sodium dodecyl sulfate enhances the wettability of the PLA microfiber fiber surface, allowing the medical dressing to further absorb wound exudate, thereby promoting wound healing. Layering polyurethane copolyester nanofiber membranes, PLA microfiber materials, and viscose fiber materials—materials with different wettability—can create a wetting gradient effect, achieving asymmetric liquid transport and enabling unidirectional moisture wicking in the medical dressing, reducing the risk of infection.
[0077] Comparative Example 1: A moisture-wicking medical dressing comprising a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 100 parts non-isocyanate polyurethane, 20 parts polyglycolic acid diol, 5 parts chain extender, and 5 parts catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0078] Non-isocyanate polyurethane and polyglycolic acid diol were poured into hexafluoroisopropanol, and chain extender sebacate chloride and catalyst triethylamine were added to obtain the reactants. The reactants were washed with deionized water and then placed in a vacuum drying oven to obtain non-isocyanate polyurethane copolyester.
[0079] Non-isocyanate polyurethane copolyester and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0080] The monolayer membrane was subjected to plasma treatment. The plasma-treated monolayer membrane was then placed on a spin coater, and a chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane.
[0081] Comparative Example 2: A moisture-wicking medical dressing comprising a polyurethane copolyester nanofiber membrane. The non-isocyanate polyurethane copolyester comprises the following components by weight: 100 parts non-isocyanate polyurethane, 20 parts polyglycolic acid diol, 5 parts chain extender, and 5 parts catalyst. The preparation method of the polyurethane copolyester nanofiber membrane includes the following steps:
[0082] Non-isocyanate polyurethane and polyglycolic acid diol were poured into hexafluoroisopropanol, and chain extender sebacate chloride and catalyst triethylamine were added to obtain the reactants. The reactants were washed with deionized water and then placed in a vacuum drying oven to obtain non-isocyanate polyurethane copolyester.
[0083] Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film.
[0084] The monolayer membrane was subjected to plasma treatment, and the plasma-treated monolayer membrane was placed on a spin coater to spin coat the surface of the monolayer membrane with spermidine crosslinking agent to obtain a polyurethane copolyester nanofiber membrane.
[0085] Performance testing
[0086] Test 1 Tensile property test: The samples prepared in Examples 1-5 and Comparative Examples 1-2 were tested using a universal testing machine. They were cut into standard dumbbell-shaped strips and tested according to the national standard GB / T 1040.1-2006. The tensile strength was recorded.
[0087] Test 2 Antibacterial performance test: The bacterial solution of the samples prepared in Examples 1-5 and Comparative Examples 1-2 was mixed with the nutrient broth on the petri dish, the sample was attached to the petri dish, and placed in a constant temperature incubator. The diameter of the inhibition zone was calculated.
[0088] Test 3 Water vapor transmission performance test: The samples prepared in Examples 1-5 and Comparative Examples 1-2 were placed in a permeation cup with a desiccant according to standard JIS1099A. The permeation cup was covered and sealed with the sample. The permeation cup was placed in a constant temperature and humidity incubator and the water vapor transmission rate was recorded.
[0089] Test 4: Swelling performance test: The samples prepared in Examples 1-5 and Comparative Examples 1-2 were cut into 2cm × 2cm pieces, and the swelling rate of the samples was calculated according to standard YY / T 0471.1-2004.
[0090] Table 1 Test results of sample performance testing
[0091] Example 1 62.24 4.2 3425.7 732.45 Example 2 56.35 3.8 3262.4 715.34 Example 3 51.43 3.4 3092.4 697.35 Example 4 47.38 3.1 2914.2 681.75 Example 5 43.64 2.8 2796.6 675.46 Comparative Example 1 60.17 2.9 3387.2 728.46 Comparative Example 2 55.35 3.9 3568.4 683.64
[0092] According to Examples 1-5, Comparative Examples 1-2 and Table 1, the introduction of levofloxacin enhances the antibacterial properties of medical dressings; non-isocyanate polyurethane copolyester improves the mechanical properties of fiber fabrics; and polyurethane copolyester nanofiber membranes have good moisture permeability and moisture absorption properties.
[0093] Working principle: By introducing non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile, levofloxacin can inhibit or kill bacteria, reduce the risk of wound infection, and achieve indirect anti-inflammatory effect. Polyacrylonitrile enhances the mechanical strength of polyurethane copolyester nanofibers and prolongs the drug release cycle.
[0094] In the molecular chain of non-isocyanate polyurethane copolyester, ether bonds form a transport path for water molecules, achieving a highly efficient moisture-wicking effect in medical dressings, preventing the accumulation of exudate at the wound site, preventing the reverse penetration of liquid water, helping the wound to heal quickly, and improving the sweating effect.
[0095] Chitosan and gelatin have good biocompatibility and can promote wound healing. Glycerin has excellent water absorption properties and can improve the moisture absorption of medical dressings. Spermidine crosslinking agent forms a stable crosslinking network structure with chitosan-gelatin-glycerin layer, ensuring stable release of spermidine during use.
[0096] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A moisture-wicking medical dressing, characterized in that: The invention includes a polyurethane copolyester nanofiber membrane, and the preparation method of the polyurethane copolyester nanofiber membrane includes the following steps: Non-isocyanate polyurethane copolyester, levofloxacin, and polyacrylonitrile were poured into hexafluoroisopropanol to obtain a spinning solution. The spinning solution was poured into a syringe for electrospinning. The spinning voltage was set to 17 kV and the feed speed was 0.7 mm / h to obtain a monolayer film. The monolayer membrane was subjected to plasma treatment, and the plasma-treated monolayer membrane was placed on a spin coater. A chitosan-gelatin-glycerol mixed solution was spin-coated onto the surface of the monolayer membrane. After drying, spermidine crosslinking agent was spin-coated to obtain a polyurethane copolyester nanofiber membrane. The preparation method of the spermidine crosslinking agent includes the following steps: Remove spermidine from the refrigerator and thaw it using a water bath. Pour terephthalaldehyde into anhydrous ethanol and stir to obtain a terephthalaldehyde solution. The thawed spermidine was poured into a terephthalaldehyde solution and stirred to obtain a spermidine crosslinking agent.
2. The moisture-wicking medical dressing according to claim 1, characterized in that: The non-isocyanate polyurethane copolyester comprises the following components by weight: 80-100 parts of non-isocyanate polyurethane, 5-20 parts of polyglycolic acid diol, 1-5 parts of chain extender, and 0.5-5 parts of catalyst. The preparation method of the non-isocyanate polyurethane copolyester includes the following steps: Non-isocyanate polyurethane and polyglycolic acid diol were poured into hexafluoroisopropanol, stirred and heated to 60°C. When no liquid dripped from the condenser outlet, chain extender and catalyst were added. Heating was stopped after 0.5 h to obtain the reactants. The reactants were washed with deionized water and then placed in a vacuum drying oven and dried at 100°C for 24 hours to obtain a non-isocyanate polyurethane copolyester.
3. The moisture-wicking medical dressing according to claim 1, characterized in that: The preparation method of the chitosan-gelatin-glycerol mixed solution includes the following steps: Chitosan powder was poured into an acetic acid aqueous solution to prepare a chitosan mixed solution. Gelatin powder was poured into deionized water to prepare a gelatin solution. The chitosan mixed solution and the gelatin solution were mixed to obtain a chitosan-gelatin mixed solution. Glycerin was added to the chitosan-gelatin mixed solution and stirred to obtain the chitosan-gelatin-glycerin mixed solution.
4. The moisture-wicking medical dressing according to claim 2, characterized in that: The preparation method of the non-isocyanate polyurethane includes the following steps: Ethylene carbonate and 1,6-hexanediamine were mixed under a nitrogen atmosphere, stirred and heated to 80°C, deionized water was added, and the mixture was frozen, recrystallized and vacuum dried to obtain hexanediamine ethylene glycol diol. Hexamethylenediamine glycol diol and polyethylene glycol were poured into a reaction vessel, stannous chloride dihydrate was added, the mixture was stirred and heated to 220°C, and vacuum pump was used for depressurization treatment to obtain non-isocyanate polyurethane.
5. The moisture-wicking medical dressing according to claim 3, characterized in that: The chitosan-gelatin mixed solution has a mass fraction ratio of chitosan to gelatin of 1:4 and a volume fraction ratio of chitosan-gelatin mixed solution to glycerol of 7:
3.
6. The moisture-wicking medical dressing according to claim 2, characterized in that: The preparation method of the polyglycolic acid diol includes the following steps: Glycolic acid and neopentyl glycol are mixed, zinc acetate dihydrate and toluene are added, nitrogen gas is introduced and the mixture is heated to 120°C to obtain polyglycolic acid diol.
7. The moisture-wicking medical dressing according to claim 2, characterized in that: The chain extender is sebacate chloride, and the catalyst is triethylamine.
8. A method for preparing a moisture-wicking medical dressing, applicable to the moisture-wicking medical dressing according to any one of claims 1-7, characterized in that: The preparation method includes the following steps: S1. Polyurethane copolyester nanofiber membrane, polylactic acid microfiber material, and viscose fiber material are sequentially stacked and subjected to hot pressing to obtain medical dressing.
9. The method for preparing a moisture-wicking medical dressing according to claim 8, characterized in that: The preparation method further includes the following steps: S11. Polylactic acid chips and molten polyethylene glycol are blended together, sodium dodecyl sulfate chips are added, and the mixture is stirred using a high-speed mixer to obtain a blended raw material. S12. The blended raw materials are melted into polymer melt by a screw extruder, and the polymer melt is transported to the spinneret hole of the die head by a metering pump. The melt is extruded into fine streams and bonded to the receiving screen to form polylactic acid microfiber material.
Citation Information
Patent Citations
Biological powder medical dressing and preparation method thereof
CN103007339B
Preparation method of composite nanofiber membrane for wound dressing and composite nanofiber membrane
CN114949325A
Janus fiber dressing with one-way drainage, photo-thermal evaporation and sterilization functions as well as preparation method and application of Janus fiber dressing
CN118059288A